PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN ULANGAN SEMESTER GENAP MELALUI RAPAT KERJA MGMP DI SMAN 1 RIAU SILIP BANGKA - AMIRULLAH AMIRULLAH (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This study aims to identify and describe the ability of teachers at SMAN 1 Riau Silip Kab. Bangka, in preparing the even semester test through the MGMP work meeting. This research is classified as a supervisory action research involving 15 teachers of social studies, Indonesian and PPKN subjects, which is used as a sample for the preparation of a summative test, based on the criteria for preparing a standardized test. From the results of the previous survey, they have never compiled a test based on the criteria / steps for preparing a standardized test. They arrange the test by adopting test questions from the question bank they have and are adjusted to the indicators of the material taught in class. Based on the criteria obtained, from cycle I and cycle II the average score showed an increase, from an average score of 65.4 to a score of 75.3. it means the efforts of the teachers of SMAN 1 Riau Silip Kab. Bangka in compiling the Deuteronomy was significant and they had put a lot of effort into being able to make a proper test. In the first cycle there were 2 teachers who had not finished, so it was continued in the second cycle to complete as well as provide enrichment for those who had completed. From the results of the analysis in cycle I and cycle II showed an increase in quality with the average result of the ability of teachers at SMAN 1 Riau Silip Kab. Bangka in compiling even semester tests from an average score of 65.4 to a score of 76.43 with an increase of 25%. Thus, it can be concluded that through the MGMP working meeting in the preparation of the even semester exams, the teachers of SMAN 1 Riau Silip Kab. Bangka , has succeeded in making a standardized test (feasible) based on the established criteria. Hopefully the teachers at SMAN 1 Riau Silip Bangka in carrying out formative tests, semester tests and school exams and others will no longer adopt the existing questions (question bank). ABSTRAKPenelitian ini bertujuan untuk mengetahi dan mendeskripsikan  kemampuan guru SMAN 1 Riau Silip Kab. Bangka, dalam menyusunan Ulangan semester genap melalui rapat kerja MGMP. Penelitian ini tergolong penelitian tindakan kepengawasan dengan melibatkan 15 orang guru mata pelajaran IPS, Bahasa Indonesia dan PPKN, yng  dijadikan sempel  penyusunan tes sumatif, berdasarkan kreteria penyusunan tes standar. Dari hasil  survai   sebelumnya mereka belum pernah menyusun  tes  berdasrkan kreteria / langkah-langkah penyusunan tes setandar.  Mereka menyusun tes dengan  mengadopsi soal tes dari bank soal yang dimiliki dan disesuaikan dengan indikataor materi yang diajarkan di kelas. Berdasarkan kreteia yang didapat, dari siklus I dan siklus II rata-rata skor menunjukkan peningkatan, dari rata-rata skor 65.4 ke skor 75.3. itu berarti upaya guru SMAN 1 Riau Silip Kab. Bangka  dalam menyusun Ulangan sudah signifikan dan  mereka sudah sangat berupaya untuk bisa membuat tes yang layak.  Dalam siklus I ada  2 orang guru belum tuntas, maka dilanjutkan  kesiklus II untuk menuntaskan sekaligus memberikan pengayaan bagi yang sudah tuntas. Dari hasil analisis pada siklus I dan siklus II menunjukkan peningkatan kualitas dengan hasil rata-rata kemampuan guru SMAN 1 Riau Silip Kab. Bangka dalam menyusun Ulangan semester genap  dari rata-rata skor  65.4 menjadi skor 76.43 dengan peningkatan sebesar  25 %. Dengan demikian dapat disimpulkan bahwa melalui  rapat kerja MGMP dalam penyusunan Ulangansemester genap Guru-guru SMAN 1 Riau Silip Kab. Bangka , telah berhasil membuat tes standar ( layak ) berdasarkan kreteria yang ditetapkan. Mudah-mudahan guru di SMAN 1 Riau Silip Bangka dalam melaksanakan tes formatif, tes semesteran dan ujian sekolah serta lainnya tidak lagi mengadosi soal yang ada ( bank soal).